Improving Secondary School Students’ Speaking Skills through Forum Group Discussion: An Action Research Study - Kamaruzzaman (CV. Yazri Aksara Nusantara, 2025)
Purpose – This study explored the effectiveness of the Forum Group Discussion (FGD) method in enhancing speaking skills among tenth-grade students at MTs NW Montong Mas. The research was motivated by persistent challenges in EFL contexts, including students’ low confidence and limited vocabulary, which often hinder oral communication. The study aimed to fill a gap in existing research by providing empirical evidence of FGD’s impact in this specific educational setting. Design/methods/approach – A qualitative classroom action research design was employed, involving oral speaking tests, classroom observations, and questionnaires. Data were collected across three phases: pre-action, Cycle I, and Cycle II, focusing on improvements in fluency, pronunciation, vocabulary, grammar, and clarity. Findings – Results showed a substantial increase in students achieving the Minimum Mastery Criterion, from 36% in the pre-action stage to 80% in Cycle II. Class average scores improved from 69.46 to 76.66, and observations noted enhanced classroom engagement and reduced speaking anxiety. Research implications/limitations – While FGD proved effective, limitations include varying student confidence levels and challenges in managing balanced discussions. Future studies are recommended to integrate digital tools and examine FGD’s effectiveness across diverse educational contexts